2021
DOI: 10.1186/s12951-021-00890-9
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of payload in extracellular vesicles by crosstalk with mesenchymal stem cells from different origin

Abstract: Background The application of extracellular vesicles (EVs) derived from mesenchymal stem cells (MSCs) requires customized materials to target disease or cell damage. We hypothesized that EVs exert different inflammatory effects on one recipient cell, although stem cells of different origins in humans have similar payloads. Results Here, the payload of EVs released by crosstalk between MSCs and human middle ear epithelial cells (HMEECs) extracted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The schematic of this diagram is to present an approach direction of exosome-based therapy (exo-therapy) for application to hearing loss (Figure 3). Stem cell derived exosomes are used for communication between cell to cell, and it is known that the payload changed depending on the origin of the stem cells [55]. It has been reported that miRNAs and proteins generated in communication between donor cells and target cells are different.…”
Section: Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The schematic of this diagram is to present an approach direction of exosome-based therapy (exo-therapy) for application to hearing loss (Figure 3). Stem cell derived exosomes are used for communication between cell to cell, and it is known that the payload changed depending on the origin of the stem cells [55]. It has been reported that miRNAs and proteins generated in communication between donor cells and target cells are different.…”
Section: Future Prospectsmentioning
confidence: 99%
“…It has been reported that miRNAs and proteins generated in communication between donor cells and target cells are different. In other words, the author believe that it may be helpful to selectively deliver interest genes to cure tissue or cells in destination using exosome with different payload [55]. The approach direction of exosome-based therapy (exo-therapy) for applying to hearing loss was described and its advantages were introduced.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Stem cells, both tendon stem/progenitor cells (TSPCs) and mesenchymal stem cells (MSCs) from other tissues, have been extensively studied in tendon healing and tendinopathy treatments [ 5 , 6 ]. Common sources of MSCs include bone marrow, fat, gums, and dental pulp; thus, it is natural that biological diversities exist among EVs derived from different MSCs [ 7 ]. Adipose tissue-derived mesenchymal stem cells (ADMSCs) demonstrate tissue repair potentials through differentiate into target cells in the injured area, secretion of various cytokines/growth factors to neighboring cells as well as immunomodulatory effects to reduce the inflammatory response in damaged tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Given the similar properties, cellderived biomimetic nanovesicles could be utilized for drug delivery [24,25], tissue regeneration [26,27], and cancer targeting [28,29]. In particular, it was reported that nanovesicles derived from human tonsil-derived mesenchymal stem cells attenuate liver fibrosis and inflammation [30,31]. However, the anti-aging effects of nanovesicles derived from human tonsil-derived mesenchymal stem cells (TMSCs) have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%